Pengembangan Sistem Informasi Pengelolaan Aset dan Barang Berbasis Web untuk Meningkatkan Efisiensi Inventaris di Perguruan Tinggi: Studi Kasus Universitas STEKOM Kampus Kendal - Asyraf Ryan Pradana, Asyraf; Sudirman, Bagus; Kamto Sudibyo, Sukemi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to design and develop a web-based Asset and Goods Management Information System (SIPAB) implemented at Universitas STEKOM, Kendal Campus. The primary issue in asset management at this institution lies in the continued use of conventional tools such as Microsoft Excel and Word, which are prone to errors and inefficiency in reporting and monitoring. The research method used is Research and Development (R&D) with the Waterfall development model. Data collection techniques include observation, interviews, and literature study. The result of this research is a web-based system comprising modules for asset data, maintenance, disposal, and reports accessible internally. The system is expected to improve the efficiency, accuracy, and security of campus asset management.